Ultrastructural analysis of parvalbumin synapses in human dorsolateral prefrontal cortex. Issue 9 (26th March 2017) - Glausier, Jill R.; Roberts, Rosalinda C.; Lewis, David A.
Abstract: Coordinated activity of neural circuitry in the primate dorsolateral prefrontal cortex (DLPFC) supports a range of cognitive functions. Altered DLPFC activation is implicated in a number of human psychiatric and neurological illnesses. Proper DLPFC activity is, in part, maintained by two populations of neurons containing the calcium‐binding protein parvalbumin (PV): local inhibitory interneurons that form Type II synapses, and long‐range glutamatergic inputs from the thalamus that form Type I synapses. Understanding the contributions of each PV neuronal population to human DLPFC function requires a detailed examination of their anatomical properties. Consequently, we performed an electron microscopic analysis of (1) the distribution of PV immunoreactivity within the neuropil, (2) the properties of dendritic shafts of PV‐IR interneurons, (3) Type II PV‐IR synapses from PV interneurons, and (4) Type I PV‐IR synapses from long‐range projections, within the superficial and middle laminar zones of the human DLPFC. In both laminar zones, Type II PV‐IR synapses from interneurons comprised ∼60% of all PV‐IR synapses, and Type I PV‐IR synapses from putative thalamocortical terminals comprised the remaining ∼40% of PV‐IR synapses. Thus, the present study suggests that innervation from PV‐containing thalamic nuclei extends across superficial and middle layers of the human DLPFC. These findings contrast with previous ultrastructural studies in monkey DLPFC where Type I PV‐IR synapses were not identified in the superficial laminar zone. The presumptive added modulation of DLPFC circuitry by the thalamus in human may contribute to species‐specific, higher‐order functions. Abstract : Using electron microscopic analyses, the authors show that parvalbumin‐immunoreactive synapses characteristic of thalamocortical inputs are present and prevalent in the superficial laminar zone of the human dorsolateral prefrontal cortex. These findings contrast with previous studies in monkeys, and may represent a human‐specific feature.